Nghiên cứu một số yếu tố ảnh hưởng đến sự hình thành vật liệu rây phân tử mao quản trung bình trật tự SBA-15 - Sơn, Lê Thanh; Khiếu, Đinh Quang (Vietnam Journal of Chemistry, 2014)
The effect of some factors on the formation of mesoporous structures of SBA-15 was investigated. SBA-15 materials were prepared by using block copolymer EO20PO70EO20 (P123) as structure-directing-agent, tetraethoxysilane (TEOS) as silica source, and concentrated HCl aqueous solution as acid source. Three series of samples were prepared to study the change trend of mesoporous structure by the variations of ratios of HCl/TEOS, P123/TEOS, H2O/TEOS. The resulting SBA-15 materials were characterized by TG-DSC, XRD, N2 physical sorption isotherms. The experiments shows that HCl/TEOS, P123/TEOS, and H2O/TEOS in the range of 7.74 - 15.5; 0.32 - 0.43; 122.93 - 159.81, respectively could provide a highly ordered mesoporous material with high surface areas.